2013
DOI: 10.1007/s12032-013-0664-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of combined cisplatin plus irinotecan chemotherapy for gastroenteropancreatic neuroendocrine carcinomas

Abstract: No standard treatment is currently available for gastroenteropancreatic neuroendocrine carcinomas (GEP-NEC). Therefore, we conducted this study to evaluate the effect of the combination of irinotecan and cisplatin in the treatment of GEP-NECs. Clinical data of 16 locally advanced or metastatic GEP-NEC patients treated with irinotecan plus cisplatin regimen in our center from September 2009 to August 2011 were reviewed. The regimen included 2-week cycles of 180 mg/m(2) irinotecan and 50 mg/m(2) cisplatin on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Alternative regimens substituting carboplatin for cisplatin, or irinotecan for EP, have been validated in SCLC and seem at least equivalent in terms of efficacy in limited series of GEP NEC (table 1) [13,30,31,32,33,34,35], with different toxicity profiles. In the context of advanced stage SCLC, a randomized study conducted in Japan demonstrated that the combination of irinotecan and cisplatin (IP) was associated with improved overall survival as compared to the standard cisplatin and EP combination [36].…”
Section: Treatmentmentioning
confidence: 99%
“…Alternative regimens substituting carboplatin for cisplatin, or irinotecan for EP, have been validated in SCLC and seem at least equivalent in terms of efficacy in limited series of GEP NEC (table 1) [13,30,31,32,33,34,35], with different toxicity profiles. In the context of advanced stage SCLC, a randomized study conducted in Japan demonstrated that the combination of irinotecan and cisplatin (IP) was associated with improved overall survival as compared to the standard cisplatin and EP combination [36].…”
Section: Treatmentmentioning
confidence: 99%
“…In our retrospective analysis of 16 advanced GEP-NEC patients treated with IP, the median PFS and OS were 5.5 and 10.6 months, respectively [17]. Recently, a retrospective Japanese multicenter analysis [25] showed that for patients with advanced NEC of the digestive system including gastrointestinal tract and hepato-biliary-pancreatic system treated with IP/EP ( n = 160/46), the ORR were 50%/28% and the median OS times were 13.0/7.3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Our retrospective study has also revealed that the ORR of IP chemotherapy was 57.1 %, with a disease control rate of 78.6 % in advanced GEP-NEC patients [17]. Although quite chemo-sensitive, advanced GEP-NECs are always aggressive with short progression-free survival (PFS) and overall survival (OS) times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response rate was 51%, median PFS 5.5 months, and OS 10.6 months. [59] A further subgroup of patients with GEP NENs G3 (WHO 2010) is represented by morphologically well-differentiated neuroendocrine neoplasms while having Ki67 > 20% and/ or mitosis > 20/10 HPF. Recent reports suggest that these tumors have a better prognosis than other GEP NECs and are less responsive to conventional chemotherapies.…”
Section: Cisplatin [Compound Danshen Dripping Pills (Cddp)]/ Etoposidmentioning
confidence: 99%